Canal 10 TV: el espejismo de la primera televisión privada de España - Mateos-pérez, Javier (Historia y Comunicación Social, 2007)
This investigation centres on the experience of Canal 10 which presents an enormous interest for it is the first national-wide private television initiative in Spain, and because it was developed while the parliamentary process of enacting television rules was taking place. For this motive, both legislators and communication businessmen suspected of the legality of the project. The investigation not only describes the path of Channel 10: it also contributes with unpublished material obtained from the in-the-day main streams of opinion, about the opinions and interests of all the agents involved in the process of the analysed period. It also gathers a summary of parliamentary discussions that condense themselves the different approaches that, together, formed the social process around this item. The case of the Canal 10 TV is important because it informs of the diverse interests —economic, managerial, political, social— that come together in the business and political configuration of private television in Spain.